AUTOMATIC CONTROL SYSTEM OF TEMPERATURE IN THE RESERVOIR FOR SANITARY TREATMENT OF HYDRO MATERIAL - I. A. Zhernosek; T. A. Rudakova; N. S. Strigun (Современная наука и инновации, 2022)
The authors offer automated control of mineral water temperature for reservoir sanitization hydro material. The authors choose the control parameters for the control system, they make a mathematical model with the regulator control system and they carry out a simulation of the closed control system on a computer. As a result of the simulation they verify the compliance of the terms of reference of quality indicators requirements control system and they made the appropriate correction parameters of the controller